The school in the face of school failure in contexts of inequity: between social mandates and medicalized responses (Praxis Educativa, 2022)
This article addresses the complex and multi-determined problem of school failure in contexts of violation of rights, providing a reading that takes up the undeniable influence that living conditions have on the development of the tools that support learning. For this we take into account our experience as health professionals who work in the field of psychomotor clinic and the review of the literature related to the subject. Although Uruguay has made important efforts in the field of inclusive education through the installation of the issue on the public agenda and the enactment of laws in this regard, the generation of conditions that ensure the effective fulfillment of the rights enshrined both at an ethical and legal level, it is still complex. To approach this issue we are interested in problematizing the hegemonic school model that has characterized Modernity, and analyzing the failed responses that are built around school failure in contexts of social inequity, among which we highlight the medicalization of school difficulties and discourses that reinforce the alleged equalizing power of the school.
Keywords: children's rights; public policies; educational inclusion; social inequality; school failure